Development of Web-based Employee Performance Appraisal Information System with SAW Method at PT Muawanah Al Ma'soem - Dina Grisela; Tedjo Darmanto; Moch Irwan Hermanto (Media Jurnal Informatika, 2025)
Employee performance appraisal at PT Muawanah Al Ma'soem is still done manually, causing problems of efficiency, accuracy, and objectivity. This research is focused on designing a web-based information system used to assess employee performance, with the aim of increasing the effectiveness and efficiency of the evaluation process. To produce an objective assessment based on a number of criteria, the Simple Additive Weighting (SAW) method is used, while the Rapid Application Development (RAD) approach is applied to accelerate system development through an iterative process and the use of prototypes. The result of the research is a web-based system with features of employee data management, assessment criteria, and automatic ranking. Tests show that the system runs well and helps speed up the assessment process and improve the accuracy of the results. The system that has been developed is proven effective in accelerating the appraisal process while maintaining objectivity in employee performance evaluation.